Green Marketing, Green Perceived Value, and Price Perception: Their Effects on Eco Bag Purchase Decisions at Alfamart Sidoarjo - Alfi Rahmawati; Siti Aminah (Manunggal Halim Jaya, 2026)
The increasing problem of plastic waste in Indonesia has encouraged retail industry players to introduce eco-friendly products such as eco bags as an alternative to single-use plastic bags. However, the declining sales of eco bags at Alfamart Sidoarjo during the 2023–2025 period indicates that the green marketing strategy implemented has not been fully effective in driving consumer purchasing decisions. This study aims to analyze the effect of green marketing, green perceived value, and price perception on the purchasing decision of eco bags at Alfamart Sidoarjo. This study employed a quantitative approach with purposive sampling technique involving 102 respondents, data collection through questionnaires, and data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results show that green marketing has a positive but insignificant effect on purchasing decisions, green perceived value has a positive and significant effect on purchasing decisions, and price perception has a positive and significant effect on purchasing decisions with the greatest contribution among the three variables examined.